The Impact of Family Conflicts on Children Education. - Edmond Ndayambaje; Yvette Umwari; Ayriza Yulia (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2020)
The current study aims at (1) identifying the factors leading to family conflicts and (2) determining the impacts of family conflict and children education in order to improve family well-being. The study involves qualitative approach with case study design. The targeted group consisted of ten participants: five females and five males. Purposive sampling technique was adapted in selecting the subjects. Concerning with the size of the sample, the researcher preferred using convenience sampling, due to the situation on the field it was absolutely difficulty to firmly fix the respondents. An open-ended questionnaire with eight components was used to develop questions connected to the scope of the study. The collected data were analysed through thematic analysis. The findings indicated that the prevailing factors of family conflicts in the region are miscommunication, mismanagement of family property, irresponsibility, and infidelity. Moreover, the majority of children of the respondents are swiftly heading to very low academic performance compared to their school achievements prior to facing the issue.